The invisible factors that can make the difference: language management and knowledge transfer in multinational sites - Albuquerque, Alexandra (2014)
The knowledge-based society we live in has stressed the importance of human capital and brought talent to the top of most wanted skills, especially for companies who want to succeed in turbulent environments worldwide. In fact, streams, sequences of decisions and resource commitments characterize the day- to-day of multinational companies (MNCs) and internationalized companies. In most companies, strategic decisions are extensively discussed and are generally formulated and articulated in specialized language often developed by the best minds in the company. Yet the language used in such deliberations is usually taken for granted and receives little attention, being often managed ad hoc. With this paper we intend to discuss some strategies that are commonly used by companies and refer some actions that can boost talent and improve language performance, in certain international communication contexts, with little investment